Positive electrode active material for all-solid-state battery, positive electrode, and all-solid-state battery
By forming a lithium titanium oxide particle layer on the surface of the positive electrode active material of a sulfide-based all-solid state battery, the side reaction problem between the positive electrode active material and the sulfide-based solid electrolyte particles is solved, and the stable charging and discharge of the battery is achieved.
Patent Information
- Application Number
- CN202480004506.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-23
- Filing Date
- 2024-09-30
- Publication Date
- 2025-06-24
AI Technical Summary
In the positive electrode of a sulfide-based all-solid state battery, physical contact between the positive electrode active material and the sulfide-based solid electrolyte particles can easily lead to side reactions, damage the active material and increase resistance.
A lithium titanium oxide particle layer is formed on the surface of the positive electrode active material, which acts as a buffer layer to prevent side reactions caused by physical contact between the positive electrode active material and the sulfide-based solid electrolyte particles.
By forming a lithium titanium oxide particle layer, damage and side reactions of the positive electrode active material can be effectively prevented, ensuring the stability of the battery during the charging and discharging process.
Smart Images

Figure CN120202556A_ABST
Abstract
Description
[Technical Field]
[0001] This application claims the priority of Korean Patent Application No. 10-2023-0141761, filed on October 23, 2023, the disclosure of which is incorporated herein by reference in its entirety.
[0002] The present invention relates to a positive electrode active material for an all-solid-state battery, a positive electrode, and an all-solid-state battery including the same. [Background Art]
[0003] Various batteries are being studied to overcome the limitations of current lithium secondary batteries in terms of capacity, safety, output, large-scale and miniaturization.
[0004] Representative examples include: metal-air batteries having a very high theoretical capacity compared to lithium secondary batteries; all-solid-state batteries without explosion risk and safe; supercapacitors in terms of output; NaS batteries or redox flow batteries (RFB) for large-scale applications; and thin-film batteries for miniaturization. These technologies are being continuously studied in academia and industry.
[0005] An all-solid-state battery is a battery in which a liquid electrolyte used in a conventional lithium secondary battery is replaced with a solid electrolyte. Since a flammable solvent is not used in the battery, there is no possibility of fire or explosion due to the decomposition reaction of the conventional electrolyte, which can significantly improve safety. In addition, in all-solid-state batteries, the technology development of sulfide-based all-solid-state batteries is ongoing. This battery has a high ionic conductivity of the solid electrolyte and can theoretically achieve a high energy density of at least 900 Wh / L. A sulfide-based all-solid-state battery refers to an all-solid-state battery containing a sulfide-based solid electrolyte.
[0006] In an all-solid-state battery system, lithium ions are not conducted through the liquid electrolyte contained in a conventional lithium-ion battery (LIB). Therefore, when manufacturing a positive electrode for a sulfide-based all-solid-state battery, it is necessary to increase the contact interface between the positive electrode active material and the sulfide-based solid electrolyte particles by adding sulfide-based solid electrolyte particles inside the positive electrode to improve the ionic conductivity of lithium ions. In addition, in order to improve the energy density, it is necessary to enhance the physical contact between the positive electrode active material, the sulfide-based solid electrolyte particles, and other cell components inside the positive electrode, and it is necessary to reduce the porosity of the positive electrode after rolling and maintain this during charge and discharge.
[0007] However, in a positive electrode for a sulfide-based solid battery, due to the level difference between the positive electrode active material and the sulfide-based solid electrolyte particles, a chemical reaction can occur only through their physical contact. In addition, side reactions occur at the interface between the positive electrode active material and the sulfide-based solid electrolyte particles, which not only consume active lithium but also increase the resistance.
[0008] Therefore, there is always a need to develop a technology that can prevent side reactions caused by physical contact between the positive electrode active material and sulfide-based solid electrolyte particles at the positive electrode of a sulfide-based all-solid-state battery.
[0009] [Prior Art Documents]
[0010] (Patent Document 1) Japanese Patent Publication No. 2009-224307 [Summary of the Invention]
[0011] [Technical Problem]
[0012] The inventors of the present invention conducted extensive research to solve the above problems and confirmed that coating the surface of the positive electrode active material with Li4Ti5O 12 particles to form a Li4Ti5O 12 particle layer, and the Li4Ti5O 12 particle layer can prevent side reactions between the positive electrode active material and sulfide-based solid electrolyte particles during physical contact between the positive electrode active material and sulfide-based solid electrolyte particles in the positive electrode, thereby enabling stable charging and discharging.
[0013] Therefore, an object of the present invention is to provide a positive electrode active material having a particle layer formed on its surface to prevent side reactions during physical contact with sulfide-based solid electrolyte particles.
[0014] Another object of the present invention is to provide a positive electrode including a positive electrode active material having a particle layer formed on its surface to prevent side reactions during physical contact with sulfide-based solid electrolyte particles.
[0015] Another object of the present invention is to provide an all-solid-state battery capable of stable charging and discharging, including a positive electrode active material having a particle layer formed on its surface to prevent side reactions during physical contact with sulfide-based solid electrolyte particles.
[0016] [Technical Solution]
[0017] To achieve the above object, the present invention provides a positive electrode active material for an all-solid-state battery, which includes a lithium titanate particle layer on its surface, wherein, in the lithium titanate particle layer, a plurality of lithium titanate particles are formed continuously or discontinuously on the surface of the positive electrode active material.
[0018] The present invention also provides a positive electrode active material for an all-solid-state battery, wherein the lithium titanate is represented by the following Chemical Formula 1:
[0019] [Chemical Formula 1]
[0020] Li x Tiy O z
[0021] Wherein, 0.5 ≤ x ≤ 5, 1 ≤ y ≤ 5, 2 ≤ z ≤ 12.
[0022] The present invention also provides a positive electrode active material for all-solid-state batteries, wherein the shape of the particles is at least one selected from the group consisting of spherical and polygonal.
[0023] The present invention also provides a positive electrode active material for all-solid-state batteries, wherein the particle size of the lithium titanium oxide particles is 10 nm to 1 μm.
[0024] The present invention also provides a positive electrode active material for all-solid-state batteries, wherein, based on the total weight of the positive electrode active material, the lithium titanium oxide particles account for not more than 5% by weight.
[0025] The present invention also provides a positive electrode active material for all-solid-state batteries, wherein the BET specific surface area of the positive electrode active material for all-solid-state batteries is 0.4 to 1 m 2 / g.
[0026] The present invention also provides a positive electrode active material for all-solid-state batteries, wherein the positive electrode active material contains at least one selected from the group consisting of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium copper oxide, and vanadium oxide.
[0027] The present invention also provides a positive electrode for all-solid-state batteries, which comprises the positive electrode active material, sulfide-based solid electrolyte particles, a conductive material, and a binder.
[0028] The present invention also provides a positive electrode for all-solid-state batteries, wherein the sulfide-based solid electrolyte is represented by the following Chemical Formula 2:
[0029] <Chemical Formula 2>
[0030] L a M b P c S d X e
[0031] Wherein, L is an element selected from the group consisting of alkali metals,
[0032] M is an element selected from the group consisting of B, Al, Ga, In, Si, Ge, Sn, Pb, As, Sb, Bi, Ti, V, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, and W,
[0033] X is an element selected from the group consisting of F, Cl, Br, I, and O, and
[0034] 0 ≤ a ≤ 12, 0 ≤ b ≤ 6, 0 ≤ c ≤ 6, 0 < d ≤ 12, 0 ≤ e ≤ 9.
[0035] The present invention also provides a positive electrode for an all-solid-state battery, wherein the conductive material includes at least one selected from the group consisting of vapor-grown carbon fiber (VGCF), graphite, carbon black, carbon fluoride, metal powder, conductive whisker, conductive metal oxide, and conductive polymer.
[0036] The present invention also provides a positive electrode for an all-solid-state battery, wherein the binder includes at least one selected from the group consisting of polytetrafluoroethylene (PTFE), polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, poly(ethylene oxide), chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, epichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate or salt, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene.
[0037] The present invention also provides an all-solid-state battery, which includes the positive electrode, a negative electrode, and a solid electrolyte membrane interposed therebetween.
[0038] [Advantageous Effects]
[0039] Due to the lithium titanate oxide particle layer formed on the positive electrode active material, the positive electrode active material according to the present invention for an all-solid-state battery can prevent damage to the positive electrode active material and can prevent side reactions between the positive electrode active material in the positive electrode and sulfide-based solid electrolyte particles.
[0040] In addition, an all-solid-state battery including a positive electrode active material formed with a lithium titanate oxide particle layer can stably charge and discharge because side reactions between the positive electrode active material and sulfide-based solid electrolyte particles can be prevented. [Brief Description of the Drawings]
[0041] Figure 1 A partial cross-sectional view of a positive electrode active material for an all-solid-state battery showing an example of an embodiment of the present invention is shown. [Detailed Description of the Embodiments]
[0042] Hereinafter, the present invention will be described in more detail to provide a better understanding.
[0043] The terms and words used in this specification and claims should not be construed in their ordinary or dictionary meanings, but should be interpreted as meanings and concepts consistent with the technical idea of the present invention based on the concept that the inventor can define the terms in a manner he deems appropriate to best illustrate his invention.
[0044] Positive electrode active material for all-solid-state battery
[0045] The present invention relates to a positive electrode active material for an all-solid-state battery.
[0046] The positive electrode active material for an all-solid-state battery of the present invention includes a lithium titanium oxide particle layer on its surface, wherein the lithium titanium oxide particle layer has a shape in which a plurality of lithium titanium oxide particles are formed continuously or discontinuously on the surface of the positive electrode active material.
[0047] Figure 1 A partial cross-sectional view of a positive electrode active material for an all-solid-state battery showing an example of the present invention is shown.
[0048] See Figure 1 , a lithium titanium oxide particle layer (20) is formed on the surface of the positive electrode active material (10). When applied to the positive electrode and present together with sulfide-based solid electrolyte particles (30), the lithium titanium oxide particle layer (20) can act as a buffer layer to prevent side reactions between them.
[0049] The lithium titanium oxide particle layer (20) can be prepared by a dry method without any solvent, and the lithium titanium oxide particles in the coating can be included in the form of particles. Therefore, the surface of the lithium titanium oxide particle layer (20) can have a continuous or discontinuous particle connection shape. A particle is a small object having physical and chemical properties.
[0050] The particles can be one or more selected from the group consisting of spherical and polygonal shapes.
[0051] The polygon can be one or more selected from the group consisting of triangle, square, pentagon, hexagon, heptagon, and octagon.
[0052] Therefore, the surface of the lithium titanium oxide particle layer can be shaped such that a curved portion having a shape of a part of a sphere and / or a polygonal portion having a shape of a part of a polygon are connected continuously and / or discontinuously.
[0053] In an example of the present invention, lithium titanium oxide (LTO) can be represented by the following Chemical Formula 1:
[0054] <Chemical Formula 1>
[0055] Li x Tiy O z
[0056] Among them, 0.5 ≤ x ≤ 5, 1 ≤ y ≤ 5, and 2 ≤ z ≤ 12.
[0057] In addition, in terms of electrochemical stability, the lithium titanium oxide can preferably be Li4Ti5O 12 .
[0058] In one example of the present invention, the particle size of the lithium titanium oxide particles can be from 10 nm to 1 μm.
[0059] Specifically, the particle size of the lithium titanium oxide particles can be 10 nm or more, 30 nm or more, or 50 nm or more, and can be 0.5 μm or less, 0.8 μm or less, or 1 μm or less. If the particle size is less than 10 nm, the interfacial resistance may increase or the dispersibility may decrease, while if the particle size is greater than 1 μm, the coverage rate of the coating may decrease.
[0060] In one example of the present invention, based on the total weight of the positive electrode active material, the lithium titanium oxide particles can account for no more than 5% by weight. In this case, the total weight of the positive electrode active material refers to the total weight of the positive electrode active material formed with the lithium titanium oxide particle layer.
[0061] Specifically, the content of the lithium titanium oxide particles can be 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, or 1% by weight or less. When the content of the lithium titanium oxide particles exceeds 5% by weight, the charge transfer resistance occurring between the positive electrode and the sulfide-based solid electrolyte particles may increase. In addition, the lower limit of the content of the lithium titanium oxide particles is not particularly limited, and can be, for example, 0.1% by weight.
[0062] In one example of the present invention, when forming the lithium titanium oxide particle layer, the BET specific surface area of the positive electrode active material for the all-solid-state battery can be from 0.4 to 1 m 2 / g.
[0063] Specifically, the BET specific surface area of the positive electrode active material for the all-solid-state battery can be 0.4 m 2 / g or more, 0.5 m 2 / g or more, or 0.6 m 2 / g or more, and can be 1 m 2 / g or less, 0.9 m 2 / g or less, 0.8 m 2 / g or less, or 0.7 m 2Less than / g. If the BET specific surface area of the positive electrode active material for the all-solid-state battery is lower than the above range, the effect of preventing side reactions between the positive electrode active material in the positive electrode and the sulfide-based solid electrolyte particles may be reduced, and if it exceeds the above range, it may act as a resistance during battery operation.
[0064] In one example of the present invention, the positive electrode active material can be any material capable of reversibly absorbing and releasing lithium ions, without particular limitation. For example, such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v O2 (where M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3 ≤ x < 1.0, 0 ≤ y, z ≤ 0.5, 0 ≤ v ≤ 0.1, x + y + z + v = 1), Li(Li a M b-a-b' M' b' )O 2-c A c (where 0 ≤ a ≤ 0.2, 0.6 ≤ b ≤ 1, 0 ≤ b' ≤ 0.2, 0 ≤ c ≤ 0.2; M contains at least one selected from the group consisting of Mn, Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' contains at least one selected from the group consisting of Al, Mg, and B; A contains at least one selected from the group consisting of P, F, S, and N), etc. layered compounds, or compounds substituted with one or more transition metals; such as the formula Li 1+y Mn 2-y O4 (where y is from 0 to 0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, or Cu2V2O7; nickel-site type lithium nickel oxides represented by the formula LiNi 1-y M y O2 (where M is Co, Mn, Al, Cu, Fe, Mg, B, or Ga, and y is from 0.01 to 0.3); lithium manganese composite oxides represented by the formula LiMn 2-y M y O2 (where M is Co, Ni, Fe, Cr, Zn, or Ta, and y is from 0.01 to 0.1) or Li2Mn3MO8 (where M is Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which a part of Li in the formula is replaced by alkaline earth metal ions; disulfide compounds; Fe2(MoO4)3, etc., but not limited thereto.
[0065] In the above-mentioned positive electrode active material for all-solid-state batteries, since a lithium titanium oxide particle layer is formed on the surface, damage to the positive electrode active material can be prevented.
[0066] In addition, when the positive electrode active material having a lithium titanium oxide particle layer is applied to the positive electrode for all-solid-state batteries, side reactions with sulfide-based solid electrolyte particles contained in the positive electrode can be prevented. In other words, the lithium titanium oxide particle layer can act as a buffer layer between the positive electrode active material and the sulfide-based solid electrolyte particles to prevent side reactions, thereby enabling stable charge and discharge of all-solid-state batteries.
[0067] Moreover, even if the surface of the positive electrode active material is coated with lithium titanium oxide particles, the bulk structure of the positive electrode active material remains unchanged, thereby enabling stable electrochemical performance. Generally, problems during the coating process of the positive electrode active material may change the bulk structure of the positive electrode active material. For example, the bulk structure may become a rock salt structure, in which case the mobility of lithium in the positive electrode active material may decrease. However, in the present invention, even when coated with lithium titanium oxide particles, the bulk structure of the positive electrode active material can still remain stable.
[0068] In addition, in the present invention, there is no problem of particles falling off from the lithium titanium oxide particle layer, which can improve the reliability of the product.
[0069] Manufacturing method of positive electrode active material for all-solid-state batteries
[0070] The present invention also relates to a method for preparing a positive electrode active material for all-solid-state batteries.
[0071] The method for preparing the positive electrode active material for all-solid-state batteries of the present invention includes: (S1) mixing the positive electrode active material with lithium titanium oxide particles; and (S2) heating and then cooling the mixture.
[0072] This method can be carried out by a dry process without using a solvent, or by a wet process in which the particles are dispersed in a solvent in step (S1) and then mixed.
[0073] Hereinafter, the manufacturing method of the positive electrode active material for all-solid-state batteries of the present invention will be described in more detail through each step.
[0074] In one example of the present invention, in the above step (S1), the positive electrode active material can be mixed with lithium titanium oxide particles.
[0075] The types and contents of the positive electrode active material and the lithium titanium oxide particles are as described above.
[0076] Alternatively, the lithium titanium oxide particles can be dispersed in a solvent and then mixed. In this case, the solvent is not particularly limited as long as it is a solvent capable of stably dispersing the lithium titanium oxide particles. For example, the solvent can be any solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methyl-2-pyrrolidone (NMP), acetone, or water, and a mixture of one or more selected therefrom can be used.
[0077] In one example of the present invention, in the above step (S2), the mixture can be heated and then cooled to coat the surface of the positive electrode active material with the lithium titanium oxide particles.
[0078] The heating temperature can be 150°C to 300°C. If the heating temperature is lower than 150°C, the adhesion between the lithium titanium oxide particles and the adhesion between the lithium titanium oxide particles and the surface of the positive electrode active material may decrease, while if the heating temperature is higher than 300°C, the lithium on the surface of the positive electrode active material may be deintercalated due to high-temperature heat treatment. Specifically, the heating temperature can be 150°C or higher, 160°C or higher, 170°C or higher, or 180°C or higher, and 220°C or lower, 240°C or lower, 260°C or lower, 280°C or lower, or 300°C or lower.
[0079] In addition, cooling the heated lithium titanium oxide particle layer can further improve the adhesion of the lithium titanium oxide particle layer and enhance the durability of the positive electrode active material itself. For example, the cooling temperature can be 10 to 30°C.
[0080] Positive electrode for all-solid-state battery
[0081] The present invention relates to a positive electrode for an all-solid-state battery.
[0082] The positive electrode for an all-solid-state battery of the present invention includes a positive electrode active material, sulfide-based solid electrolyte particles, a binder, and a conductive material.
[0083] In one example of the present invention, the positive electrode can be in a form without a current collector. In this case, the positive electrode active material layer containing the positive electrode active material, sulfide-based solid electrolyte particles, a binder, and a conductive material can itself be used as the positive electrode.
[0084] Alternatively, the positive electrode can include a positive electrode current collector and a positive electrode active material layer formed on one side of the positive electrode current collector. The positive electrode active material layer can contain the positive electrode active material, sulfide-based solid electrolyte particles, a conductive material, and a binder.
[0085] The positive electrode current collector supports the positive electrode active material layer and functions to transfer electrons between the external wire and the positive electrode active material layer.
[0086] The positive current collector is not particularly limited as long as it has high electronic conductivity without causing chemical changes in the all-solid-state battery. For example, stainless steel, aluminum, nickel, titanium, palladium, calcined carbon, stainless steel with its surface treated with carbon, nickel or silver, aluminum-cadmium alloy, etc. can be used as the positive current collector.
[0087] The positive current collector may have a micro-concave-convex structure or a three-dimensional porous structure on its surface to enhance the bonding force with the positive active material layer. Therefore, the positive current collector can include various forms such as films, sheets, foils, sieves, meshes, porous materials, foams, and non-woven fabric materials.
[0088] In one example of the present invention, the positive active material is the positive active material having a lithium titanium oxide particle layer formed on its surface as described above.
[0089] The positive active material is as described above.
[0090] Moreover, based on the total weight of the positive active material layer, the content of the positive active material can be 55 to 90% by weight. Specifically, the content of the positive active material can be 55% by weight or more, 60% by weight or more, or 65% by weight or more, and 83% by weight or less, 85% by weight or less, or 90% by weight or less. If the content of the positive active material is less than 55% by weight, the battery performance may decrease, and if the content is higher than 90% by weight, the mass transfer resistance may increase.
[0091] In one example of the present invention, sulfide-based solid electrolyte particles can be included in the positive electrode to improve the ionic conductivity.
[0092] The sulfide-based solid electrolyte can be represented by the following Chemical Formula 2:
[0093] <Chemical Formula 2>
[0094] L a M b P c S d X e
[0095] Wherein, L is an element selected from the group consisting of alkali metals,
[0096] M is an element selected from the group consisting of B, Al, Ga, In, Si, Ge, Sn, Pb, As, Sb, Bi, Ti, V, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, and W,
[0097] X is an element selected from the group consisting of F, Cl, Br, I, and O, and
[0098] 0 ≤ a ≤ 12, 0 ≤ b ≤ 6, 0 ≤ c ≤ 6, 0 < d ≤ 12, 0 ≤ e ≤ 9.
[0099] For example, sulfide solid electrolytes may include those selected from the group consisting of Li6PS5Cl, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is one of Ge, Zn, and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In), and Li 10 GeP2S 12 at least one selected from the group consisting of.
[0100] Moreover, based on the total weight of the positive electrode active material layer, the content of the sulfide solid electrolyte may be 10 to 50% by weight. Specifically, the content of the sulfide solid electrolyte may be 10% by weight or more, 20% by weight or more, or 30% by weight or more, and may be 40% by weight or less, 45% by weight or less, or 50% by weight or less. If the content of the sulfide solid electrolyte particles is less than 10% by weight, the effect of enhancing ionic conductivity may not be significant, while if it is higher than 50% by weight, the content of the positive electrode active material, binder, or conductive material may be relatively reduced, resulting in a decline in battery performance.
[0101] In one example of the present invention, a binder may be included to promote the bonding between the materials contained in the positive electrode active material layer and the bonding between the positive electrode active material layer and the positive electrode current collector.
[0102] The binder may include at least one selected from the group consisting of polytetrafluoroethylene (PTFE), polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, epichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate or salt, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and polyvinylidene fluoride - hexafluoropropylene. Preferably, the binder may include polytetrafluoroethylene (PTFE).
[0103] Moreover, based on the total weight of the positive electrode active material layer, the content of the binder may be 0.1 to 3% by weight. Specifically, the content of the binder may be 0.1% by weight or more, 0.5% by weight or more, 0.8% by weight or more, or may be 1.5% by weight or less, 2% by weight or less, or 3% by weight or less. If the content of the binder is less than 0.1% by weight, the effect of improving the binding force between the materials contained in the positive electrode active material layer is extremely small, and the electrode sheet may not be formed properly. If the content is greater than 3% by weight, the ionic conductivity or electrical conductivity may be reduced.
[0104] In one example of the present invention, a conductive material may be included in the positive electrode to improve ionic conductivity.
[0105] In addition, the conductive material is not particularly limited as long as it can prevent side reactions in the internal environment of the all - solid - state battery and has excellent electrical conductivity without causing chemical changes in the battery. Representative graphite or conductive carbon can be used. For example, the following materials can be used alone or as a mixture of two or more: graphite such as natural graphite, artificial graphite, etc.; carbon black such as acetylene black, Ketjen black, Denka black, thermal - cracked carbon black, channel black, furnace black, lamp black, summer carbon black, etc.; carbon - based materials having a graphene or graphite crystal structure; conductive fibers such as carbon fiber, metal fiber, etc.; carbon fluoride; metal powders such as aluminum powder, nickel powder, etc.; conductive whiskers such as zinc oxide, potassium titanate, etc.; conductive metal oxides such as titanium oxide, etc.; and conductive polymers such as polyphenylene derivatives, etc., but not necessarily limited thereto. Preferably, the conductive material may include vapor - grown carbon fiber (VGCF).
[0106] Based on the total weight of the positive electrode active material layer, the content of the conductive material may be from 0.1% by weight to 5% by weight. More specifically, the content of the conductive material may be 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, 2% by weight or more, 4% by weight or less, 4.5% by weight or less, or 5% by weight or less. If the content of the conductive material is too small, less than 0.1% by weight, it is difficult to expect the effect of improving the conductivity or the electrochemical performance of the battery may deteriorate. If it is too much, exceeding 5% by weight, the amount of the positive electrode active material is relatively small, resulting in a decrease in capacity and energy density.
[0107] All-solid-state battery
[0108] The present invention relates to an all-solid-state battery including a solid electrolyte membrane.
[0109] The all-solid-state battery of the present invention includes a positive electrode, a negative electrode, and a sulfide-based solid electrolyte membrane interposed therebetween. The positive electrode is as described above.
[0110] In one example of the present invention, the negative electrode includes a negative electrode active material layer, wherein the negative electrode active material layer may be formed on one side of the negative electrode current collector.
[0111] The negative electrode active material layer may include a negative electrode active material, a conductive material, and a binder. Alternatively, the negative electrode active material layer may be a non-negative electrode layer.
[0112] In the negative electrode active material layer, the negative electrode active material may include a material capable of reversibly inserting or extracting lithium (Li + ), a material capable of reacting with lithium ions to reversibly form a lithium-containing compound, lithium metal, or a lithium alloy.
[0113] A material capable of reversibly inserting or extracting lithium ions (Li + ) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. A material capable of reacting with lithium ions (Li + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of indium (In), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0114] Preferably, the negative electrode active material may be lithium metal or a lithium-indium alloy (Li-In). More specifically, it may be in the form of lithium metal, a lithium thin film, a lithium-indium alloy thin film, or powder.
[0115] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be 40 to 80% by weight. Specifically, the content of the negative electrode active material can be 40% by weight or more, 50% by weight or more, or can be 70% by weight or less or 80% by weight or less. If the content of the negative electrode active material is less than 40% by weight, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if the content is higher than 80% by weight, the mass transfer resistance may be large.
[0116] The binder is a component that aids in the binding of the negative electrode active material to the conductive material or to the negative electrode current collector, and may include at least one selected from the group consisting of styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, poly(ethylene oxide), chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, epichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate or salt, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene. Preferably, the binder may include polytetrafluoroethylene (PTFE).
[0117] Moreover, based on the total weight of the negative electrode active material layer, the content of the binder can be 0.5% by weight to 4% by weight. More specifically, the content of the binder can be 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, 3% by weight or less, 3.5% by weight or less, or 4% by weight or less. If the binder content is less than 0.5% by weight, the adhesion of the negative electrode active material to the negative electrode current collector may decrease, and if the binder content is greater than 4% by weight, the adhesion may be improved, but the content of the negative electrode active material may decrease, resulting in a lower cell capacity.
[0118] In addition, there is no particular limitation on the conductive material, as long as it can prevent side reactions in the internal environment of the all-solid-state battery and has excellent conductivity without causing chemical changes in the battery. Representative materials such as graphite or conductive carbon can be used. For example, the following materials can be used alone or in a mixture of two or more: graphites such as natural graphite and artificial graphite; carbon blacks such as carbon black, acetylene black, Ketjen black, Denka black, thermal cracking carbon black, channel black, furnace black, lamp black, summer carbon black; carbon-based materials with a graphene or graphite crystal structure; conductive fibers such as carbon fiber and metal fiber; carbon fluorides; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives; but it is not necessarily limited thereto. Preferably, the conductive material may include vapor-grown carbon fiber (VGCF).
[0119] Moreover, based on the total weight of the negative electrode active material layer, the content of the conductive material may be 1 wt% to 5 wt%. More specifically, the content of the conductive material may be 1 wt% or more, 1.5 wt% or more, 2 wt% or more, and may be 4 wt% or less, 4.5 wt% or less, or 5 wt% or less. If the content of the conductive material is too small, for example, less than 1 wt%, it is difficult to expect the effect of improving conductivity or the electrochemical performance of the battery may deteriorate. If it is too much, for example, more than 5 wt%, the amount of the negative electrode active material may be relatively small, resulting in a decrease in capacity and energy density. The method of introducing the conductive material into the negative electrode is basically not limited, and any conventional method known in the art can be adopted, such as mixing with the negative electrode active material or coating the negative electrode active material.
[0120] In addition, there is no particular limitation on the negative electrode current collector, as long as it has conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel with a surface treated with carbon, nickel or silver, aluminum cadmium alloy, etc. can be used. In addition, like the positive electrode current collector, the negative electrode current collector can be in various forms with fine concavities and convexities formed on the surface, such as films, sheets, foils, meshes, porous materials, foams, non-woven fabric materials, etc.
[0121] The manufacturing method of the negative electrode is not particularly limited, and it can be manufactured by forming a negative electrode active material layer on the negative electrode current collector using a conventional layer or film formation method. For example, methods such as pressing, coating, or deposition can be adopted. The negative electrode of the present invention also includes the case where a metal lithium film is formed on a metal plate through initial charging after assembling the battery without a lithium film on the negative electrode current collector.
[0122] In addition, a non-lithium anode layer means an anode layer that does not contain lithium metal or lithium alloy that can serve as a source of lithium in the anode active material at the initial assembly of the battery, but lithium is deposited in the anode through charging. A battery containing such a non-lithium anode layer can be referred to as a non-lithium anode battery.
[0123] In a non-lithium anode battery, during the charge and discharge process of the battery, lithium ions released from the cathode migrate to the anode to form an anode active material layer. For example, during the charging process of the battery, lithium ions are released from the cathode active material and migrate to the anode side to form lithium metal composed only of lithium, forming a lithium metal layer on the anode current collector, or forming any other form of lithium metal structure other than a layer form. Any other form may refer to, for example, a structure in which lithium metal aggregates in the form of particles.
[0124] In one example of the present invention, the sulfide-based solid electrolyte contained in the sulfide-based solid electrolyte layer can be represented by the following Chemical Formula 2.
[0125] <Chemical Formula 2>
[0126] L a M b P c S d X e
[0127] Wherein, L is an element selected from the group consisting of alkali metals,
[0128] M is an element selected from the group consisting of B, Al, Ga, In, Si, Ge, Sn, Pb, As, Sb, Bi, Ti, V, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, and W,
[0129] X is an element selected from the group consisting of F, Cl, Br, I, and O, and
[0130] 0 ≤ a ≤ 12, 0 ≤ b ≤ 6, 0 ≤ c ≤ 6, 0 < d ≤ 12, 0 ≤ e ≤ 9.
[0131] For example, sulfide-based solid electrolytes may include at least one selected from the group consisting of Li6PS5Cl, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is one of Ge, Zn, and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In), and Li 10 GeP2S 12 formed.
[0132] However, the sulfide-based solid electrolytes are not limited to these, and a wide range of sulfide-based solid electrolytes commonly used in the art can be used.
[0133] Battery module
[0134] The present invention also relates to a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0135] Specific examples of the device include, but are not limited to: power tools powered by an electric motor; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV); electric two-wheel vehicles, including electric bicycles (E-bike) and electric scooters (E-scooter); electric golf carts; and energy storage systems, etc.
[0136] [Examples]
[0137] Hereinafter, preferred embodiments of the present invention will be described for the purpose of illustrating the present invention. However, it is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical idea of the present invention, and such changes and modifications fall within the scope of the appended patent claims.
[0138] In the following examples and comparative examples, a positive electrode active material, a positive electrode including the positive electrode active material, and an all-solid-state battery were prepared as described in Table 1 below.
[0139] [Table 1]
[0140]
[0141] Example 1
[0142] 1-1. Preparation of the positive electrode active material having a lithium titanium oxide particle layer on the surface
[0143] As described in Table 1 above, a mixture was obtained by mixing 99% by weight of the positive electrode active material with 1% by weight of lithium titanium oxide. The particle size of the lithium titanium oxide was 50 nm.
[0144] The above mixture was heated to a temperature of 200 °C and then cooled, and the surface of the positive electrode active material was coated with lithium titanium oxide particles to form a lithium titanium oxide particle layer.
[0145] 1-2. Preparation of the positive electrode
[0146] The positive electrode active material having a lithium titanium oxide particle layer formed thereon, sulfide-based solid electrolyte particles, a conductive material, and a binder were powder-mixed at a weight ratio of 83.8:14.8:0.2:1.2. Specifically, the positive electrode active material and the sulfide-based solid electrolyte Li6PS5Cl were quantified in powder form and mixed in a dry indoor environment using a blade mixer for 15 minutes to obtain a mixture. Then, powder of vapor-grown carbon fiber (VGCF) as the conductive material was quantitatively added to the mixture and mixed, and powder of polytetrafluoroethylene (PTFE) as the binder was quantitatively added and further mixed to obtain a mixed powder.
[0147] After putting the mixed powder into a mortar, fibrillation was carried out in the mortar and rolling was performed with a roller, thereby preparing a positive electrode with a loading amount of 6 mAh / cm 2 of the positive electrode.
[0148] 1-3. All-solid-state battery
[0149] The positive electrode, the sulfide-based solid electrolyte membrane (Li6PS5Cl), and the negative electrode (lithium metal) were stacked in sequence and pressed to 100 Mpa, thereby preparing an all-solid-state battery.
[0150] Example 2
[0151] Except that the heat treatment temperature was set to 500 °C after mixing the positive electrode active material with the lithium titanium oxide particles, the same method as in Example 1 was carried out.
[0152] Example 3
[0153] Except that the particle size of the lithium titanium oxide particles was 2 μm, the same method as in Example 1 was adopted.
[0154] Example 4
[0155] The same method as in Example 1 was used except that the lithium titanate oxide particles were 10% by weight.
[0156] Experimental Example 1: Performance Evaluation of All-Solid-State Battery
[0157] The performance of the all-solid-state batteries separately fabricated in the examples and comparative examples was evaluated.
[0158] The capacity performance of the all-solid-state battery was observed using the following protocol: The battery was activated 2 cycles at 0.05C in a charge-discharger and then discharged up to 1C. Specifically, the rate performance was observed using a protocol of charging at 0.05C CC / CV (constant current / constant voltage) and discharging at 0.05C CC for 2 cycles, then charging at 0.1C CC / CV but discharging at CC at 0.1C / 0.2C / 0.33C / 0.5C / 1C.
[0159] Table 2 below shows the results of the all-solid-state battery performance evaluation.
[0160] [Table 2]
[0161]
[0162] As can be seen from Table 2, Example 1 has excellent initial Coulomb efficiency, capacity retention at 100 cycles, and capacity retention at 1C retention.
[0163] On the other hand, Examples 2 to 4 all showed relatively lower initial Coulomb efficiency, capacity retention at 100 cycles, and capacity retention at 1C compared to Example 1.
[0164] Example 2 was heat-treated at a higher temperature. Among them, due to the deterioration of the positive electrode active material at a higher temperature, the initial Coulomb efficiency and capacity retention were relatively reduced.
[0165] In addition, the particle size of the lithium titanate oxide particles in Example 3 was relatively large, reducing the coverage rate on the surface of the positive electrode active material and unable to inhibit the side reactions occurring at the interface between the positive electrode active material and the solid electrolyte particles, resulting in relatively low initial Coulomb efficiency and capacity retention.
[0166] In addition, Example 4 showed that a relatively high content of lithium titanate oxide particles caused excessive coverage on the positive electrode surface, resulting in poor interfacial conductivity, thus leading to a relatively low initial Coulomb efficiency and a relatively low capacity retention at 1C.
[0167] [Reference Signs]
[0168] 10: Positive electrode active material
[0169] 20: Lithium titanium oxide particle layer
[0170] 30: Sulfide-based solid electrolyte particles
Claims
1. A positive electrode active material for an all-solid-state battery, comprising a lithium titanium oxide particle layer on the surface, in, In the lithium titanium oxide particle layer, a plurality of lithium titanium oxide particles are continuously or discontinuously formed on the surface of the positive electrode active material.
2. The positive electrode active material for an all-solid-state battery according to claim 1, in, The lithium titanium oxide is represented by the following chemical formula 1: <Chemical Formula 1> Li x You y ON z Among them, 0.5≤x≤5, 1≤y≤5, 2≤z≤12.
3. The positive electrode active material for an all-solid-state battery according to claim 1, in, The shape of the particles is at least one selected from the group consisting of spheres and polygons.
4. The positive electrode active material for an all-solid-state battery according to claim 1, in, The particle size of the lithium titanium oxide particles is 10 nm to 1 μm.
5. The positive electrode active material for an all-solid-state battery according to claim 1, in, The lithium titanium oxide particles account for no more than 5 wt % based on the total weight of the positive electrode active material.
6. The positive electrode active material for an all-solid-state battery according to claim 1, in, The BET specific surface area of the positive electrode active material for the all-solid-state battery is 0.4 to 1 m 2 / g.
7. The positive electrode active material for an all-solid-state battery according to claim 1, in, The positive electrode active material includes at least one selected from the group consisting of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium copper oxide, and vanadium oxide.
8. A positive electrode for an all-solid-state battery, comprising the positive electrode active material according to claim 1, sulfide-based solid electrolyte particles, a conductive material and a binder.
9. The positive electrode for an all-solid-state battery according to claim 8, in, The sulfide-based solid electrolyte is represented by the following chemical formula 2: <Chemical Formula 2> L a M b P c S d X e wherein L is an element selected from the group consisting of alkali metals, M is an element selected from the group consisting of B, Al, Ga, In, Si, Ge, Sn, Pb, As, Sb, Bi, Ti, V, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta and W, X is an element selected from the group consisting of F, Cl, Br, I and O, and 0≤a≤12,0≤b≤6,0≤c≤6,0 <d≤12,0≤e≤9。 10. The positive electrode for an all-solid-state battery according to claim 8, in, The conductive material includes at least one selected from the group consisting of vapor grown carbon fiber (VGCF), graphite, carbon black, carbon fluoride, metal powder, conductive whisker, conductive metal oxide and conductive polymer.
11. The positive electrode for an all-solid-state battery according to claim 8, in, The binder includes at least one selected from the group consisting of polytetrafluoroethylene (PTFE), polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylic acid ester or salt, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.
12. An all-solid-state battery comprising the positive electrode according to claim 8, a negative electrode and a sulfide-based solid electrolyte membrane interposed therebetween.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery and method for manufacturing the same
JP2009224307A
Tire production method and device
KR1020230141761A
Cited By
Sulfide composite solid electrolyte membrane and preparation method thereof
CN121688074A